Analysis of UMKM Traders’ Perceptions and Adoption of QRIS-Based Digital Marketing in Banyuasri Traditional Market, Singaraja - Dewa Gede Darmayasa; I Nengah Suarmanayasa; Ni Luh Wayan Sayang Telagawathi (Amkop Management Accounting Review (AMAR), 2026)
The rapid development of digital technology in the era of Society 5.0 has significantly transformed various sectors, including the economic sector. One of the innovations supporting digital transactions in Indonesia is the Quick Response Code Indonesian Standard (QRIS), which integrates multiple digital payment systems into a single standardized platform. This study aims to analyze the perceptions of Micro, Small, and Medium Enterprises (MSMEs) traders regarding the implementation of QRIS in Banyuasri Singaraja Traditional Market.   This research employs a qualitative approach with a phenomenological perspective. Data were collected through observations and in-depth interviews with MSME traders who utilize QRIS in their transaction activities. The data were analyzed using the interactive model of data analysis, including data reduction, data presentation, and conclusion drawing.   The results indicate that MSME traders perceive QRIS as beneficial in improving transaction efficiency and effectiveness, enhancing business professionalism and image, and expanding digital marketing opportunities. In terms of ease of use, QRIS is considered practical, flexible, and universal, enabling transactions anytime and anywhere. However, several obstacles were identified, including dependence on internet connectivity, limited signal availability, and challenges in withdrawing digital balances into cash. In conclusion, QRIS plays a significant role in supporting the digital transformation of MSMEs in traditional markets. Despite its advantages, continuous support in the form of digital literacy training and infrastructure improvement is necessary to optimize its implementation and enhance MSME competitiveness in the digital economy era.